Kompetensi Pedagogik dan Profesional Guru PAI dalam Efektivitas Manajemen Pembelajaran Agama di MAN 2 Model Kota Medan - Siregar, Bahtiar; Tumiran, Tumiran; manshuruddin, Manshuruddin; Mardinsyah, Aziz (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze the influence of pedagogical and professional competence of Islamic Religious Education (PAI) teachers on the effectiveness of religious learning management at MAN 2 Model Medan. The research employs a quantitative approach with a correlational design. Data were collected through questionnaires distributed to 30 PAI teachers at MAN 2 Model Medan, covering aspects of pedagogical competence, professionalism, and the effectiveness of learning management. The results show that both pedagogical and professional competence of PAI teachers have a significant impact on the effectiveness of religious learning management. Teachers with strong pedagogical competence are able to create more effective teaching strategies, while their professionalism supports the overall success of the learning process. Based on these findings, it is recommended that the school continue to enhance the training and development of PAI teachers’ competencies to improve the quality of religious learning management at the school.